Characterization and genetic variability analysis in Capsicum annuum L. germplasm (SAARC Journal of Agriculture, 2014)
Fifty three genotypes of Capsicum annuum L. collected from different parts of the West Bengal, India were characterized for 23 characters namely, stem colour, plant growth habit, branching habit, leaf size, leaf shape, leaf margin, leaf colour, leaf pubescence, pigment at node, flower per axil, corolla colour, anther colour, calyx margin, mature fruit colour at intermediate stage, fruit shape, fruit position, fruit adherence to the calyx, fruit shape at pedicel attachment, blossom end fruit shape, ascorbic acid content of the fruit, capsaicin in red fruit and colour value of the ripe fruit. These genotypes upon cataloguing showed distinct variations with respect to vegetative, inflorescence, fruit and quality characters. A wide range of variation was also observed among the genotypes for several morphological, fruit and quality characters. Among the different characters, white corolla colour showed 100 % frequency and higher frequency was also recorded in single flower per axil (86.79 %), number pigmentation at node (83.02 %) and green fruit colour (69.81%) at intermediate stage. Predominance of single descriptor state was found in more than 50 % genotypes for 15 characters. Based on the D2 value 53 genotypes were grouped into 17 clusters and results indicated that Cluster I and Cluster VII comprised with 29 and 9 genotypes respectively. Rest of clusters consisted of one genotype in each case. Variability studies revealed that there was a wide range of variability for all the characters studied. High heritability along with higher genetic advance (as a %age of mean) was found in capsaicin content in fruit, number of fruits per plant, yield per plant and primary branches per plant. These characters may be considered as reliable selection indices as they are possibly governed by additive gene effect. DOI: http://dx.doi.org/10.3329/sja.v11i1.18387 SAARC J. Agri., 11(1): 91-103 (2013)